2016
DOI: 10.1093/ehjqcco/qcw039
|View full text |Cite
|
Sign up to set email alerts
|

Increased incidence of infective endocarditis after the 2009 European Society of Cardiology guideline update: a nationwide study in the Netherlands

Abstract: This observational study shows that there has been a steady increase in the IE incidence between 2005 and 2011. After the introduction of the 2009 ESC guidelines, the incidence increased more than expected from previous historical trends. Furthermore, there was a significant increase in streptococci-related IE cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
56
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 15 publications
7
56
1
4
Order By: Relevance
“…Similar limitations to those discussed in this review applied to both studies, one of which reported no impact of the guideline31 and the other a negative impact reflected in a significant increase in streptococci-related IE cases 32…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Similar limitations to those discussed in this review applied to both studies, one of which reported no impact of the guideline31 and the other a negative impact reflected in a significant increase in streptococci-related IE cases 32…”
Section: Discussionmentioning
confidence: 63%
“…Since this systematic review was completed, at least two further studies have been published aimed at determining the impact of antibiotic prophylaxis guideline changes on the incidence of IE 31 32. Similar limitations to those discussed in this review applied to both studies, one of which reported no impact of the guideline31 and the other a negative impact reflected in a significant increase in streptococci-related IE cases 32…”
Section: Discussionmentioning
confidence: 86%
“…We must however state that none of the deaths were directly contributed to the described technique. A large portion of the patients suffered from infective endocarditis, of which mortality ranges from 30% to 60% . Also three patients died of natural causes at home, of who two were over 80 years old which is a normal life expectancy in the Netherlands.…”
Section: Discussionmentioning
confidence: 97%
“…A large portion of the patients suffered from infective endocarditis, of which mortality ranges from 30% to 60%. 17,18 Also three patients died of natural causes at home, of who two were over 80 years old which is a normal life expectancy in the Netherlands. One patient developed a SIRS reaction.…”
Section: Discussionmentioning
confidence: 99%
“…Since the paradigm change in the guidelines regarding AP starting in 2007, several studies have tried to investigate the effect of this shift in the incidence of endocarditis. Some studies failed to show an increase in the incidence of IE after the introduction of the new guidelines (2)(3)(4)(5), whereas other studies have raised concerns regarding increasing incidence of IE (6)(7)(8)(9). In the face of a lack of randomized controlled trials regarding AP, all previously mentioned studies will inevitably have methodological errors which hinder drawing scientifically rigorous conclusions.…”
mentioning
confidence: 99%